“Get the DNR”: residents’ perceptions of goals of care conversations before and after an e-learning module - Branfield Day, Leora; Saunders, Stephanie; Steinberg, Leah; Ginsburg, Shiphra; Soong, Christine (Canadian Medical Education Journal, 2021)
Background: Residents frequently lead goals of care (GoC) conversations with patients and families to explore patient values and preferences and to establish patient-centered care plans. However, previous work has shown that the hidden curriculum may promote physician-driven agendas and poor communication in these discussions. We previously developed an online learning (e-learning) module that teaches a patient-centered approach to GoC conversations. We sought to explore residents’ experiences and how the module might counteract the impact of the hidden curriculum on residents’ perceptions and approaches to GoC conversations. Methods: Eleven first-year internal medicine residents from the University of Toronto underwent semi-structured interviews before and after completing the module. Themes were identified using principles of constructivist grounded theory. Results: Prior to module completion, residents described institutional and hierarchical pressures to “get the DNR” (Do-Not-Resuscitate), leading to physician-centered GoC conversations focused on code status, documentation, and efficiency. Tensions between formal and hidden curricula led to emotional dissonance and distress. However, after module completion, residents described new patient-centered conceptualizations and approaches to GoC conversations, feeling empowered to challenge physician-driven agendas. This shift was driven by greater alignment of the new approach with their internalized ethical values, greater tolerance of uncertainty and complexity in GoC decisions, and improved clinical encounters in practice. Conclusion: An e-learning module focused on teaching an evidence-based, patient-centered approach to GoC conversations appeared to promote a shift in residents’ perspectives and approaches that may indirectly mitigate the influence of the hidden curriculum, with the potential to improve quality of communication and care.